An Efficient Transformation Method for the Bioplastic‐Producing "Knallgas" Bacterium Ralstonia eutropha H16. Issue 11 (5th September 2017) - Tee, Kang Lan; Grinham, James; Othusitse, Arona M.; González‐Villanueva, Miriam; Johnson, Abayomi O.; Wong, Tuck Seng
Abstract : Ralstonia eutropha H16 (also known as Cupriavidus necator H16) is a Gram‐negative lithoautotrophic β‐proteobacterium with increasing biotechnological applications, including carbon capture and utilization, biopolymer synthesis, and biofuel production. Engineering of this organism is supported by the availability of its genome sequence and suitable plasmid systems. However, the lack of a simple and robust transformation method remains a challenge as it limits both the pace and ease of engineering this organism. To overcome this limitation, a systematic study is performed to evaluate the effects of different parameters on the transformation efficiency of R. eutropha H16. The optimized electroporation protocol uses R. eutropha H16 cells grown to OD600 0.6. These cells are made competent by a 15‐min incubation in 50 mM CaCl2, followed by two cell washes and final resuspension in 0.2 M sucrose prior to electroporation using 2.3 kV. This protocol achieves a transformation efficiency of (3.86 ± 0.29) × 10 5  cfu µg −1 DNA, a 10 3 ‐fold improvement compared to a previously published value for the same plasmid. This transformation method is a valuable tool for R. eutropha H16 research and will further enable the development of other advanced molecular biology methods for this industrially relevant microorganism. Abstract : Ralstonia eutropha H16 is a β‐proteobacterium that can utilize CO2 as carbon source; a property that renders it an attractive microorganism for sustainable biological production of chemicals and fuels. In this work, the authors develop a highly efficient electroporation method with at least 100‐fold improvement over previous protocols by optimizing all the transformation parameters. This work will expedite engineering efforts of R. eutropha H16 and stimulate development of more molecular biology tools to facilitate its investigation.